PEMANFAATAN TEKNOLOGI DIGITAL DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Naila Saadah Ramadhani Naila Saadah Ramadhani; Yeni Ega Susanti; Bambang Saputra (Lembaga Sepercenter, 2025)
The very rapid The advancement of digital technology has profoundly transformed numerous facets of life, particularly within the education sector. In this contemporary digital age, the integration of digital technology into the learning process is becoming an increasingly important element. Elementary schools, as the foundation of formal education, play a strategic role in preparing students to face future challenges. However, the integration of digital technology in learning at the elementary school level still faces various challenges. The use of digital technology in learning at the elementary school level provides various potentials, including expanding access to learning resources, increasing student learning motivation, and facilitating better learning. interactive and personal. However, the implementation of digital technology in the learning context also faces various challenges, including the digital divide, limited adequate infrastructure, and the lack of competence of educators in utilizing technology optimally.